An Analysis Of The Patterns Of Use, Motivation And Incidence In The Area Of Ipoh - Kong, Lee Yuen (Pusat Pengajian Ilmu Kemanusiaan, 1984)
This study examines the patterns of language use, motivation and incidence in bilingualism among the teenagers from the area of Ipoh. A sample of 110 respondents has been selected randomly from the teenage population in Ipoh. The main lang uages spoken by them are Bahasa Malaysia, Chinese, Tamil and English. Five domains such as the personal, friends and peer group, education and school, recreation and family domains will be covered by the survey in order to study the relationships between the language(s) and the teenagers.